Seed Priming with Silicon Improves Plant Resistance to Downy Mildew (Bremia lactucae) in Lettuce Seedlings by Intensifying Antioxidant Defense Systems - de Cássia Alves, Rita [UNESP]; dos Santos Zucco, Maria Fernanda [UNESP]; Oliveira, Kevein Ruas; Checchio, Mirela Vantini [UNESP]; Franco, Carolina Andrade [UNESP]; Körösi, Katalin; Gratão, Priscila Lupino [UNESP] (Springer Nature, 2022)
Lettuce cultivation occurs throughout the year in tropical countries such as Brazil. However, the most favorable time for its cultivation is also favorable to some diseases, mainly lettuce downy mildew (Bremia lactucae), limiting its commercial production. This study aimed to show the viability of silicon (Si) as an inducer of resistance to lettuce downy mildew through a biochemical approach focused on the antioxidant responses of plants. Seeds were first sterilized in a solution of sodium hypochlorite (5%), rinsed three times and pre-treated or not with Si. Seed primming with Si (calcium silicate—CaSiO3) was used for this experiment, where Si application was performed by soaking or not the seeds in a Si (CaSiO3) solution (100 μmol L−1) for one hour before germination. Three-day old germinated seedlings were then further inoculated with lettuce downy mildew (SPBl:01 race) by spraying an sporangia suspension (5 × 104 mL−1) until run-off. Treatments were formed as following: seed priming with bidistilled water and non-inoculated seedlings (Control), seed priming with bidistilled water and inoculated seedlings (Inoculated), and seed priming with Si and inoculated seedlings (Inoculated + Si). The experiment was carried out under a completely randomized design (three treatments and five replicates—consisting of 50 seedlings). Plant growth, photosynthetic pigments (total chlorophyll and carotenoids) contents were measured. MDA and H2O2 content were also quantified, as well as the activity of major antioxidant enzymes (SOD, APX, GPX and GR). Our results showed that Si reduced disease incidence, increased photosynthetic pigments contents, maintained seedling growth, reduced MDA and H2O2 contents and increased the activity of the antioxidant enzymes SOD, APX and GPX. Therefore, Si triggered seedlings resistance to lettuce downy mildew by inducing enzymatic antioxidant defense systems, mainly in the peroxidases group, such as APX and GPX.
Keywords: Antioxidant activity; Defense system; Downy mildew; Induced resistance; Lactuca sativa